Retroperitoneal Extraovarian Fibrothecoma Mimicking a Malignant Epithelial Ovarian Carcinoma - Patrick Roberts; Sharon Nofech-Mozes; Natalie Coburn; Paul Hamilton; Lilian T. Gien (Case Reports in Obstetrics and Gynecology)
Background. Fibrothecomas are benign sex cord-stromal tumors which rarely originate outside of the ovary. To date, two such cases have been reported in the literature. We report the third case of an extraovarian fibrothecoma and the first presenting similarly to a metastatic epithelial ovarian cancer. Clinical History. We describe a 62-year-old woman with history, physical examination, and imaging suggestive of metastatic ovarian cancer. CA-125 was elevated at 1291 U/mL. Paracenteses were negative for malignant cells and core biopsy showed spindle cell proliferation. A primary debulking surgery for a presumed ovarian cancer was planned. Method and Results. At surgery, 6 liters of ascites were drained. The uterus, ovaries, peritoneum, and omentum were normal. An 18×11×7 cm retroperitoneal mass was found between the left ureter and the sigmoid mesocolon, wrapped with sigmoid colon. Fallopian tubes and ovaries were normal. The mass was resected en bloc with the sigmoid colon, uterus, ovaries, and omentum. Microscopically, there was spindle cell proliferation typical of fibrothecoma. No ovarian tissue was identified in association with the tumor. Conclusion. This third case of extraovarian fibrothecoma highlights the importance of obtaining histologic evidence of malignancy prior to initiating neoadjuvant chemotherapy for a presumed ovarian cancer.